Bare Life and Biopolitics in El Rey de La Habana. Issue 1 (2nd January 2023) - McKay, Micah
Abstract: In this essay, I propose a reading of Pedro Juan Gutiérrez's novel El Rey de La Habana (1999) as a critique of the reduction of political life to what philosopher Giorgio Agamben calls "bare life." The novel, written during the período especial highlights the state of emergency and economic crisis that overwhelmed Cuba following the fall of the Berlin Wall and the dissolution of the Soviet Union. My analysis centers on Reynaldo, the novel's protagonist, and the various ways he embodies the thresholds or zones of indistinction that constitute bare life. In Agamben's terms, Reynaldo exhibits the traits of homo sacer, the sacred man whose exclusion from political life is constitutive of modern sovereign power. In this sense, my biopolitical reading contemplates the central role of excessive corporeality in the novel as an index of the violence of sovereign power during Cuba's Special Period.